Nonionic surfactant vesicular systems for effective drug delivery-an overview - Gannu P. Kumar; Pogaku Rajeshwarrao (Elsevier, 2011)
Vesicular systems are a novel means of drug delivery that can enhance bioavailability of encapsulated drug and provide therapeutic activity in a controlled manner for a prolonged period of time. Liposomes were the first such system but they suffer from a number of drawbacks including high cost and lack of stability at various pHs. Niosomes are a nonionic surfactant vesicular system, which can be easily and reliably made in the laboratory. Many factors affect noisome formation such as the method of manufacture, nature of surfactant and encapsulated drug, temperature at which the lipids are hydrated and the critical packing parameter. This review describes all aspects of niosomes including their different compositions, the various methods of preparation, the effect of changing manufacturing parameters, methods of characterization, factors that affect their stability, their use by various routes of administration, their therapeutic applications and the most important patents. The review also provides detailed information of the various types of niosomes that provide effective drug delivery.